An unceasing problem: soil-transmitted helminthiases in rural Malaysian communities - Al-Mekhlafi, M.S.; Atiya, A.S.; Lim, Y.A.L.; Mahdy, A.K.; Ariffin, W.A.; Abdullah, H.C.; Surin, Johari (SEAMEO Regional Tropical Medicine and Public Health Network, 2007)
Despite great development in socioeconomic status throughout 50 years of independence, Malaysia is still plagued with soil-transmitted helminthiases (STH). STH continue to have a significant impact on public health particularly in rural communities. In order to determine the prevalence of STH among rural Orang Asli children and to investigate the possible risk factors affecting the pattern of this prevalence, fecal samples were collected from 292 Orang Asli primary schoolchildren (145 males and 147 females) age 7-12 years, from Pos Betau, Kuala Lipis, Pahang. The samples were examined by Kato-Katz and Harada Mori techniques. Socioeconomic data were collected using pre-tested questionnaires. The overall prevalence of ascariasis, trichuriasis, and hookworm infections were 67.8, 95.5 and 13.4, respectively. Twenty-nine point eight percent of the children had heavy trichuriasis, while 22.3 had heavy ascariasis. Sixty-seven point seven percent of the children had mixed infections. Age > 10 years (p = 0.016), no toilet in the house (p = 0.012), working mother (p = 0.040), low household income (p = 0.033), and large family size (p = 0.028) were identified as risk factors for ascariasis. Logistic regression confirmed low income, no toilet in the house and working mother as significant risk factors for ascariasis. The prevalence of STH is still very high in rural Malaysian communities. STH may also contribute to other health problems such as micronutrient deficiencies, protein-energy malnutrition and poor educational achievement. Public health personnel need to reassess current control measures and identify innovative and integrated ways in order to reduce STH significantly in rural communities.